Dampak Komersialisasi Pendidikan terhadap Kesenjangan Sosial - Novi Yuliati; Ahmad Husnul Wahab; Ahmad Alfan Darmawan (Institut Kariman Wirayudha Sumenep, 2024)
In the era of globalization, the commercialization of education has become a very significant phenomenon. This research aims to explore the impact of commercialization on social inequality. The research method used is library research by critically and in-depth reviewing library materials that are relevant to the paper material such as books and journals that are suitable as references. The results of this research show that the commercialization of education makes social inequality stronger through several mechanisms, including access to quality education, social class differentiation, and societal divisions. However, there are also some arguments that commercialization of education can increase access to education and create opportunities for individuals from economically disadvantaged backgrounds. Therefore, a deeper understanding of the local context and the mechanisms involved is necessary to effectively manage the impacts of educational commercialization and reduce social inequalities.